Konsentrasi Katalis CaO dari Cangkang Telur Ayam pada Proses Transesterifikasi Biodiesel Minyak BijiPangi - Syahrial Efendi; Farida Hanum Hamzah; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to obtain best consentration of CaO catalyst chicken eggshell in transesterification process on quality of biodiesel produced from pangi seed oil. The treatment of CaO catalyst consentrations in this research were S1 (1%), S2 (1.5%), S3 (2%), S4 (2.5%), and S5 (3%). The collected data were statistically analyzed by using Analysis of Variance (ANOVA) continued by Duncan’s New Multiple Range Test (DNMRT) test at 5% level. The parameters observed were acid value, density, iodium value, saponification value, and cetana number. The results of analysis showedthat consentration of CaO catalyst chicken eggshell gaveunsignificantlyaffect on acid value and cetana number but significantly affect on density, iodium value, saponification valueof biodiesel. The chosen treatment in this research was S5 (CaO catalyst 3%). The treatment of S5 has yield 97.989% with characteristics acid value 0.682 mg KOH/g, density 885.220 kg/m3, iodium value 81.414 g I2/100 g, saponification value 179.00 mg KOH/g, and cetana number 58.473.  Keywords: biodiesel, catalyst CaO, pangi seed oil